Critical Analysis of Islamic Education Leadership Based on the Trem and Ideal Leadership Characteristics (Leadership Practice KH Hamdani Abu Bakran Adz-Zakiy) - Siti Fraisya (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2018)
This paper is intended to reveal the basic theories of Islamic educational leadership. From the definition of Islamic education leadership, the ideal terms and characteristics as a leader of Islamic education. The characteristics and conditions of leadership Islamic education have been applied in the KH Hamdani Abu Bakran Adz-zakiy leadership in Raudatul Muttaqin Islamic boarding school. He is a preacher and Islamic boarding school leader capable of influencing positive changes to his students. KH Hamdani explains the term as a leader must be able to influence others, must have strong integrity, and an ability to problem-solving. The characteristic of an Islamic Education Leader is Kharisma. The author wanted the leadership of Islamic education (except Islamic boarding school) can use the culture of the terms and characteristics of Islamic boarding school leadership, especially that has been applied by KH Hamdani Abu Bakran Adz-zakiy leadership. The results showed that the ideal Islamic leadership has been applied by KH Hamdani. This leadership can be a role model and practiced at the same time by other Islamic educational institutions, such as madrasa. So as the leadership of Islamic education is not only labeled Islam but it really implements the true Islamic leadership.